2019
DOI: 10.1136/bmjopen-2017-021098
|View full text |Cite
|
Sign up to set email alerts
|

HeART of Stroke: randomised controlled, parallel-arm, feasibility study of a community-based arts and health intervention plus usual care compared with usual care to increase psychological well-being in people following a stroke

Abstract: IntroductionPeople often experience distress following stroke due to fundamental challenges to their identity.ObjectivesTo evaluate (1) the acceptability of ‘HeART of Stroke’ (HoS), a community-based arts and health group intervention, to increase psychological well-being; and (2) the feasibility of a definitive randomised controlled trial (RCT).DesignTwo-centre, 24-month, parallel-arm RCT with qualitative and economic components. Randomisation was stratified by centre and stroke severity. Participant blinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 76 publications
0
42
3
Order By: Relevance
“…Feasibility studies of arts-based interventions in other patient groups have reported relatively low recruitment rates in terms of the proportion of eligible patients successfully recruited, with a recent feasibility study exploring a community arts-based intervention for patients who have experienced stroke reporting a recruitment rate of 14% (56/392). [43] However, in comparison our proportional recruitment rate of 25.5% (24/94) was notably higher, suggesting that there are contextually different factors that facilitate recruitment in haemodialysis settings.…”
Section: Discussionmentioning
confidence: 63%
“…Feasibility studies of arts-based interventions in other patient groups have reported relatively low recruitment rates in terms of the proportion of eligible patients successfully recruited, with a recent feasibility study exploring a community arts-based intervention for patients who have experienced stroke reporting a recruitment rate of 14% (56/392). [43] However, in comparison our proportional recruitment rate of 25.5% (24/94) was notably higher, suggesting that there are contextually different factors that facilitate recruitment in haemodialysis settings.…”
Section: Discussionmentioning
confidence: 63%
“…Suggested strategies included demonstration of the intervention at the bedside during recruitment, or inclusion of examples of completed artistic work included in the participant information sheets. Feasibility studies of arts-based interventions in other patient groups have reported relatively low recruitment rates in terms of the proportion of eligible patients successfully recruited, with a recent feasibility study exploring a community arts-based intervention for patients who have experienced stroke reporting a recruitment rate of 14% (56/392) [42]. However, in comparison our proportional recruitment rate of 25.5% (24/94) was notably higher, suggesting that there are contextually different factors that facilitate recruitment in haemodialysis settings.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility studies of arts-based interventions in other patient groups have reported relatively low recruitment rates in terms of the proportion of eligible patients successfully recruited, with a recent feasibility study exploring a community artsbased intervention for patients who have experienced stroke reporting a recruitment rate of 14% (56/392). [41] However, in comparison our proportional recruitment rate of 25.5% (24/94) was notably higher, suggesting that there may be contextually different factors that facilitate recruitment in haemodialysis settings.…”
Section: Discussionmentioning
confidence: 61%